PERENCANAAN STRATEGIS DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR - Ali Wahyudi; Imamuddin Said; Rinda Afriyani; Ngurah Ayu Nyoman Murniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Problems and challenges in the education system in Indonesia are unavoidable, especially at the elementary education level. Existing problems must be resolved immediately considering that they will have an impact on school operations and the quality of education in schools. Strategic planning is a very important role in creating a specific action plan in solving problems in an organization. This study is a literature review that aims to determine the challenges, processes or stages and impacts of strategic planning in elementary education units using the PRISMA flow. After searching for articles through the Google Scholar database, 7 articles were obtained that met the research criteria. The results of the review concluded that the challenges of strategic planning are: inaccuracy in decision making, limited time, funds and human resources and results that are not in accordance with objectives. This study found four strategic planning processes, namely: considering the vision, mission, goals and objectives of the organization, involving stakeholders in strategic planning, implementing program management and evaluating the internal and external environment. The impact of strategic planning is to improve school performance and managerial efforts so as to create elementary education units that can determine goals in the future.